Kualitas Kartu Geometri Berbasis Augmented Reality Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Rahayu, Etika Gustri; Widodo, Sri Adi; Masjid, Akbar Al; jatmiko, Jatmiko (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This study aims to determine the validity and practicality of the mathematics building card learning media using Augmented Reality technology to improve critical thinking skills. This study uses the design and development stages. The design stage aims to design a prototype of the mathematics building card using Augmented Reality technology. In contrast, the development stage seeks to test the validity and practicality of the mathematics building card using Augmented Reality technology. The subjects involved in the study were seven validators in the expert validation activity and 11 people in the product practicality activity. Data analysis used V Aiken for expert validation, while practicality used the percentage of practicality. The expert validation results showed that the V Aiken calculation results were more than 0.76 for each item. The practicality results obtained a percentage for each statement item of more than 77.27. Based on these results, it can be concluded that the mathematics building card learning media product using Augmented Reality technology can be categorized as valid and practical. The results of this study imply that research products need to be further researched, such as testing the effectiveness of the resulting product.